2008
DOI: 10.1002/er.1415
|View full text |Cite
|
Sign up to set email alerts
|

Second law analysis of two-stage compression transcritical CO2heat pump cycle

Abstract: Because of the global warming impact of hydro fluorocarbons, the uses of natural refrigerants in automotive and HVAC industries have received worldwide attention. CO 2 is the most promising refrigerant in these industries, especially the transcritical CO 2 refrigeration cycle. The objective of this work is to identify the main factors that affect two-stage compression transcritical CO 2 system efficiency. A second law of thermodynamic analysis on the entire twostage CO 2 cycle is conducted so that the exergy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…С этой целью были разработаны технологии, базирующиеся не только на эффективном использовании традиционных энергоносителей, но и предложены новые подходы, обеспечивающие вовлечение в сферу практи-ческого освоения нетрадиционные и возобновляемые энергоресурсы (энергия солнца, ветра, геотермальная энергия, тепловая энергия терриконов, нефтяных и га-зовых скважин, выработавшие свой ресурс). Некото-рые из указанных разработок приведены в [8][9][10][11][12][13][14]. Эта информация является составной частью базы данных, формирование и регулярное пополнение которой необ-ходимо для выбора конкретных технических приложе-ний для реализации интеграционной модели развития территориально-промышленных комплексов.…”
Section: методика анализа резервов энерго-и ресурсосбереженияunclassified
“…С этой целью были разработаны технологии, базирующиеся не только на эффективном использовании традиционных энергоносителей, но и предложены новые подходы, обеспечивающие вовлечение в сферу практи-ческого освоения нетрадиционные и возобновляемые энергоресурсы (энергия солнца, ветра, геотермальная энергия, тепловая энергия терриконов, нефтяных и га-зовых скважин, выработавшие свой ресурс). Некото-рые из указанных разработок приведены в [8][9][10][11][12][13][14]. Эта информация является составной частью базы данных, формирование и регулярное пополнение которой необ-ходимо для выбора конкретных технических приложе-ний для реализации интеграционной модели развития территориально-промышленных комплексов.…”
Section: методика анализа резервов энерго-и ресурсосбереженияunclassified
“…Ozgur [11] performed a theoretical simulation of an intercooler cycle and determined the optimum discharge pressure for various gas cooler outlet temperatures. Ozgur and Bayrakci [12] studied the effect of the intermediate pressure on performance and concluded that there was an optimum intermediate pressure that maximized both first-law and second-law efficiencies. Cecchinato et al [13] studied the split, flash, and intercooler systems experimentally, and confirmed that the optimum intermediate pressure deviated from the classical estimate by examining different intermediate pressures at specific discharge pressures.…”
Section: Introductionmentioning
confidence: 99%
“…A similar strategy can be found in Zubair et al (1996). Besides (Khan and Zubair, 1998), thermodynamic models of the two-stage system were developed to simulate system performance in accordance with the intermediate stage temperature and heat-exchanger parameter (installation with flash intercooling was considered as well); in Özgür and Bayrakçi (2008); the effects of temperature changes in the condenser and evaporator on the plant's irreversibility rate were determined (flash intercooling was taken into account one more time). Finally (Nikolaidis and Probert, 1998), the second-law efficiency, coefficient of cooling performance and total Exergy Destruction (ED) of the system variations with the inter-stage pressure are presented graphically, this study presents the first-and second-law analyses of the transcritical two-stage cycle with external intercooling.…”
Section: Introductionmentioning
confidence: 99%